Redesain Kompleks Kantor Kelurahan Desa Caturharjo, Kabupaten Bantul dengan Pendekatan Arsitektur Lokal - Seputra, Jackobus Ade Prasetya (Jurnal Riset Daerah, 2022)
The objective of this community service is to establish high performance and comfortable local administrative office in Caturharjo Village, Bantul, Special District of Yogyakarta. This program is intended to better accomodate current activities by redesigning local village office complexes in 2021. The design requirements are conserving existing building mass to minimize construction cost and implementing Javanese traditional style to enhance local identity as well as to fulfill new government’s rule demanding every state office should implement uniform architectural syle reflecting its local values. To achieve these goals, parametric study using Rhinoceros - Grasshopper is conducted to determine the best site layout when new building mass and parking area are added. Moreover, indoor room layout and building facades are designed conservatively by drawing digital sketches with local Javanese style. Keywords: Local Architecture, Parametric Study, Space Planning.